Pengaruh Pembelajaran Matematika Dengan Model Problem Based Learning (PBL) Dan Project Based Learning (PjBL) Terhadap Prestasi Belajar Ditinjau Dari Komunikasi Matematis Pada Siswa Kelas VIII Smp Negeri 2 Colomadu Tahun Ajaran 2015/2016 - Renny Aisyah, Rusdiana; , Dra.Sri Sutarni, M.Pd; , Sri Rejeki, M.Pd, M.Sc (2016)
The aim of this study is to find out: (1) The effect of Problem Based Learning (PBL) model and Project Based Learning (PjBL) model on learning achievement students of class VII SMP Negeri 2 Colomadu, (2) The effect of mathematical communication skill on learning achievement students of class SMP Negeri 2 Colomadu, (3) The effect of interaction between Problem Based Learning (PBL) model and Project Based Learning (PjBL) model, and mathematical communication skill on learning achievement students of class VII SMP Negeri 2 Colomadu. This is an experiment with a quasi experimental design. The population of this study was all seven graders of SMP Negeri 2 Colomadu in the even semester of academic year 2015/2016. The sample of this study was sudents two classes, consisting 36 students for the experimental class and 35 students for the control class. The sampling technique used in this study was cluster random sampling. The Methods used for collecting the data were test, questionnaires and documentation. The data were analyzed by using analysis of variance with two different cell lines. Based on the data analysis with 5% of significant level, it can be concluded that: (1) There is an effect of Problem Based Learning (PBL) model and Project Based Learning (PjBL) model on students' mathematics learning achievement. The students who were treated with Problem Based Learning (PBL) model in their learning process showed higher academic achievement than those who are treated with Project Based Learning (PjBL) model, (2) There is effect of mathematical communication skill on students' mathematics learning achievement. The students who have better mathematical communication skill showed higher academic achievement compare to those who have moderate or poor mathematical communication, (3) There is no interaction between Problem Based Learning (PBL) model and Project Based Learning (PjBL) model viewed from mathematical communication skill on students' mathematics learning achievement.